The Effect of the RQANI Learning Model on Self-Efficacy of Pre-Service Biology Teachers in Ternate City, Indonesia - Amin, Astuti Muhammad (FKIP Universitas Lampung, 2023)
Preliminary studies show that teachers did not present biology topics in context or linked them to Islamic values. Objective: The purpose of this study was to identify the effect of the RQANI model on the self-efficacy of biology students in Ternate City, North Maluku, Indonesia. Methods: The present study was a quasi-experimental study with a non-equivalent control group design. The study population contained all students from the Department of Biology Education in the city of Ternate, North Maluku, Indonesia. The sample consisted of 120 biology education students from IAIN Ternate and STIKIP Kie Raha, the city of Ternate, North Maluku. The data were collected through survey and observation. Data analysis involved descriptive and inferential statistics. Findings: The study results showed that the RQANI learning model had an effect on biology students’ self-efficacy. Conclusion: RQANI learning model had an effect on biology students’ self-efficacy Keywords: biologi students’, learning model, rqani, self-efficacy.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202312